Analisis Kesalahan Siswa dalam Menyesaikan Soal pada Materi Statistika Kelas XII IPS SMA Negeri 1 Kota Tambolaka - Laga, Ariyanti Ubu; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Student error in learning mathematics is valid in presenting data in the form of frequency distribution tables in statistical material at the high school level. These mistakes can be in the form of errors in identifying the problem, understanding the meaning of the problem, and the purpose of the problem, errors in writing the correct formula and errors in calculating the result. The purpose of this study is to describe the mistakes made by students in solving problems in statistical material. This research is a type of qualitative descriptive research. The subject of this study is students of grade XII IPS SMAN 1 Tambolaka City, and the object of research Analysis of student errors in solving problems on statistical material. The data analysis technique in research is in several steps, namely: the first step students are asked to do the problem, the second step of student work results is analyzed with the aim of finding out what mistakes students make in solving the problem, and the last step is to identify the type of student error to find out the factors causing the error. From the results of the study showed that there were three types of mistakes made by students, namely concept errors, errors in writing the correct formula and errors in calculating the result. These errors are caused by students not being careful in reading the questions, not understanding the steps of presenting data in the form of frequency distribution tables